Embodied Methods in Critical Health Communication - Laura L. Ellingson (Frontiers in Communication, 2019)
At the center of critical questions posed about power and health communication are issues of embodiment—whose bodies are judged to be healthy and whose are not, which identities are affirmed and privileged and which are stigmatized and marginalized, which material practices are pathologized and which are lauded. Critical health communication (CHC) research may be enacted by critical-interpretive researchers who employ critical embodiment theorizing frameworks that guide their questions posed, co-construction of data, and forms of analysis and representation. CHC researchers are uniquely poised to attend to the embodied aspects of health, illness, health care delivery, and public health in order to improve the health of local and global communities.